Extractive Spectrophotometric Methods for the Determination of Etoricoxib in Tablets - Kamal Shah; Alka Gupta; Pradeep Mishra (E-Journal of Chemistry)
Two simple, rapid, sensitive, precise and economic spectrophotometric methods have been developed for the estimation of etoricoxib in tablet formulation. During the course of study, it was observed that acidic solution of the drug formed colored ion-association complexes with Bromocresol Green (BCG) and Bromocresol Purple (BCP) which were soluble in chloroform. This property of the drug was followed for the development of colorimetric methods for analysis of drug. The complex of etoricoxib with BCG and BCP showed λmax at 416 nm and 408 nm respectively. These methods were validated statistically. Recovery studies gave satisfactory results indicating that none of common additives and excipients interfere the assay method. The proposed methods are found to be simple, accurate and reproducible that was successfully applied for the analysis of tablet formulation.